Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment